Women and the urban labour market in nigeria (2000)
Nigeria is a rapidly urbanizing Country with tremendous potentials for a more sophisticated urban labour market. This paper examines issues that limit women's access to formal jobs in urban sector, identifying issues like domestic responsibilities, education and gender roles amongst others as casual factors to the existing situation. I conclude by advocating for an easier access for women into formal urban labour market.